Bimetal Sb and Al co-doped synergistically modified O3 type nickel-manganese-based sodium ion battery positive electrode material and preparation method thereof
The O3-type nickel-manganese-based sodium-ion battery cathode material was prepared through a bimetallic Sb and Al co-doping synergistic modification method, which solved the problems of poor cycle performance and insufficient interface stability of existing materials, achieving high specific capacity and excellent cycle stability. stability and good rate performance.
Patent Information
- Application Number
- CN202411602692.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-01-21
AI Technical Summary
The poor circulation performance and insufficient interface stability of existing sodium ion battery cathode materials limit their application in the field of large-scale energy storage.
Through the dual -metal SB and AL, the co -doped modification method of the O3 nickel -manganese -based sodium ion battery is prepared to improve the reversible capacity, cycle stability, and interface stability of the material.
It significantly improves the ratio of the material, circulating performance, interface stability, and magnification performance, and is suitable for large -scale industrialization.
Smart Images

Figure CN119340372A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of preparation of sodium ion battery electrode materials, and specifically relates to a bimetallic Sb and Al co-doped synergistically modified O3 type nickel-manganese-based sodium ion battery positive electrode material and a preparation method thereof. Background Art
[0002] With the growing demand for energy storage, lithium-ion batteries have attracted much attention due to their advantages such as high energy density and long cycle life. However, due to the uneven distribution of lithium ore and the increasing demand for lithium ore resources and the continuous rise in prices, people are overwhelmed and can only start looking for other rechargeable batteries to replace lithium-ion batteries. Sodium-ion batteries, with their widely distributed and low-cost sodium resources, have regained widespread attention in the field of large-scale energy storage and are considered to be the best alternative to lithium-ion batteries. Compared with negative electrode materials and electrolytes, positive electrode materials play a decisive role in the electrochemical properties of batteries, such as energy density. Therefore, it is extremely important to develop positive electrode materials with long cycle life, high reversible specific capacity, and excellent sodium ion diffusion capacity. O3-type transition metal layered oxides (TMOs) have attracted much attention due to their low cost and high specific capacity. However, the widespread practical application of TMOs is limited by their inherent factors, such as poor cycle performance and insufficient interface stability.
[0003] In order to improve the electrochemical performance of TMOs, we synthesized a new type of Sb and Al co-doped cathode material through a bimetallic synergistic modification method. Doping with high-valent Sb elements can promote Ni 2+ / Ni 3+ In addition, Al doping can increase the bond energy of TM-O bonds, thereby improving the material's cycle stability, air stability, and the formed Al 2 O 3 The film reduces the contact between the material and the electrolyte, thereby improving the interface stability and inhibiting the formation of by-products, thereby increasing the Na + dynamics. Summary of the invention
[0004] The purpose of the present invention is to provide a bimetallic Sb and Al co-doped synergistically modified O3 type nickel-manganese-based sodium ion battery positive electrode material and a preparation method thereof, and to improve the preparation method of the existing sodium ion battery positive electrode material. The method can improve the specific capacity of the positive electrode material, inhibit the slip of the transition metal layer, maintain the stability of the interface, and increase the sodium ion migration rate of the material, thereby effectively improving the cycle performance and rate performance of the material, and is suitable for large-scale industrialization.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] A method for preparing a bimetallic Sb and Al co-doped synergistically modified O3 type nickel-manganese-based sodium ion battery positive electrode material comprises the following steps:
[0007] 1) Dissolve sodium salt, nickel salt, manganese salt, M salt, Sb source and Al source in deionized water respectively, and stir continuously; the sodium salt, nickel salt, manganese salt, M salt, Sb source and Al source are prepared according to the chemical formula Na x (Ni a Mn b M c )Sb d Al e O 2, Where x, a, b, c, d, e are molar numbers, 0.78<x<1, 0.2<a<1, 0.2<b<1, 0.2<c<1, 0<d<1, 0<e<1, a+b+c+d+e=1;
[0008] 2) After the metal salt in step 1) is dissolved, the weighed additive is added, and the mixture is stirred and evaporated to dryness at 100-120° C. to obtain a wet gel;
[0009] 3) vacuum drying and grinding the wet gel obtained in step 2), sintering at 450-550° C. for 6-8 hours under different atmospheres, and then sintering at 900-950° C. for 12-16 hours, with the heating and cooling rates both being 1-10° C. / min; cooling to room temperature to obtain a bimetallic Sb and Al co-doped synergistically modified O3-type nickel-manganese-based sodium ion battery positive electrode material;
[0010] 4) Similarly, for the pure phase O3 type nickel-manganese based sodium ion battery positive electrode material, no Sb source and Al source are added in step 1, and the remaining steps are the same, thereby obtaining the pure phase O3 type nickel-manganese based sodium ion battery positive electrode material.
[0011] Furthermore, in step 1), the sodium salt, nickel salt, manganese salt and M salt are all one or more of acetate, nitrate and sulfate.
[0012] Furthermore, in step 1), M is one or more metal ions selected from Cu, Fe, Mg, Zn, Ti and Co.
[0013] Furthermore, in step 1), the Sb source is one or more of antimony oxide and antimony chloride.
[0014] Furthermore, in step 1), the Al source is one or more of aluminum nitrate and aluminum oxide.
[0015] Furthermore, in step 2), the additive is one or more of citric acid, ethylene glycol and tartaric acid; the amount of the additive is 10 to 50% of the mass of the metal salt.
[0016] Furthermore, in step 3), the temperature of the vacuum drying is 120-130°C.
[0017] Furthermore, in step 3), the different atmospheres are air atmosphere, oxygen atmosphere or argon atmosphere.
[0018] The present invention prepares Sb and Al co-doped modified O3 type nickel-manganese-based sodium ion battery positive electrode material through a simple sol-gel method, high temperature solid phase sintering reaction and bimetallic synergistic doping modification. Doping with high-valent Sb elements can promote Ni 2+ / Ni 3+ In addition, Al doping can increase the bond energy of TM-O bonds, thereby improving the material's cycle stability, air stability, and the formed Al 2 O 3 The film improves the interface stability by reducing the contact between the material and the electrolyte. Therefore, the use of bimetallic Sb and Al co-doping to synergistically modify the O3-type nickel-manganese-based sodium ion battery positive electrode material can effectively improve the material's specific capacity, cycle performance, interface stability and rate performance.
[0019] The beneficial effects of the technical solution are:
[0020] 1. The present invention prepares Sb and Al co-doped modified O3 type nickel-manganese-based sodium ion battery positive electrode material through simple sol-gel preparation, high temperature solid phase sintering reaction and bimetallic synergistic doping modification. Doping with high-valent Sb elements can promote Ni 2+ / Ni 3+ In addition, Al doping can increase the bond energy of TM-O bonds, thereby improving the material's cycle stability, air stability, and the formed Al 2 O 3 The film reduces the contact between the material and the electrolyte, thereby improving the interface stability and inhibiting the formation of by-products, thereby increasing the Na + dynamics.
[0021] 2. The preparation method of the present invention is simple, efficient, low-cost, easy to realize large-scale industrialization, and is suitable for the practical application of sodium ion batteries in the future. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The X-ray powder diffraction (XRD) patterns of the Sb and Al co-doped synergistically modified O3 type nickel-manganese based sodium ion battery positive electrode material obtained in Example 1 of the present invention and the pure phase O3 type nickel-manganese based sodium ion battery positive electrode material in the comparative example are shown.
[0023] Figure 2The scanning electron microscope (SEM) images of the Sb and Al co-doped synergistically modified O3 type nickel-manganese-based sodium ion battery positive electrode material (B) obtained in Example 1 of the present invention and the pure phase O3 type nickel-manganese-based sodium ion battery positive electrode material (A) in the comparative example are shown.
[0024] Figure 3 A comparison chart of the first cycle charge and discharge curves at 0.1C of the Sb and Al co-doped synergistically modified O3 type nickel-manganese-based sodium ion battery positive electrode material obtained in Example 1 of the present invention and the pure phase O3 type nickel-manganese-based sodium ion battery positive electrode material in the comparative example is shown.
[0025] Figure 4 The figure shows the cycling performance comparison of 100 cycles at 1C rate between the Sb and Al co-doped synergistically modified O3 type nickel-manganese-based sodium ion battery positive electrode material obtained in Example 1 of the present invention and the pure phase O3 type nickel-manganese-based sodium ion battery positive electrode material in the comparative example.
[0026] Figure 5 A comparison chart of the rate performance at different rates of the Sb and Al co-doped synergistically modified O3 type nickel-manganese-based sodium ion battery positive electrode material obtained in Example 1 of the present invention and the pure phase O3 type nickel-manganese-based sodium ion battery positive electrode material in the comparative example is shown. DETAILED DESCRIPTION
[0027] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments:
[0028] Example 1
[0029] (1) According to the synthesis of 10g of Na(Ni 1 / 2 Mn 1 / 2 ) x Sb y Al z O 2 The molar ratio of Mn, Ni, Sb and Al elements in (x+y+z=1) was calculated by weighing the corresponding manganese acetate, nickel acetate, antimony oxide and aluminum oxide, respectively, and dissolved in 200 mL of deionized water. 7.48 g of sodium acetate (2% excess) was added and magnetic stirring was performed. After the transition metal salt was dissolved, 1 g of citric acid was weighed and added to the solution. The solution was evaporated to dryness under magnetic stirring at 100°C to obtain a wet gel.
[0030] (2) The wet gel obtained in step (1) is vacuum dried at 120°C, ground, sintered at 450°C for 6 hours in an argon atmosphere, and then sintered at 900°C for 12 hours, with the heating and cooling rates both being 2°C / min. After cooling to room temperature, NaNMSA, a Sb and Al co-doped synergistically modified O3-type nickel-manganese-based sodium ion battery positive electrode material, is obtained.
[0031] (3) X-ray powder diffraction (XRD) analysis shows that the obtained product NaNMSA maintains a similar structure to pure NaNM and both belong to the O3-type layered structure with a space group of R-3m. In addition, both have high crystallinity (e.g. Figure 1 As shown). From the scanning electron microscope (SEM) image, we can see that the NaNM material has a plate-like morphology and is aggregated in large quantities. At the same time, a large amount of NiO phase is precipitated on the surface. After modification, the surface is smooth and the NiO impurity phase is reduced, indicating that the synergistic modification of Sb and Al co-doping inhibits the precipitation of NiO phase and has an important influence on the subsequent electrochemical performance (such as Figure 2 shown).
[0032] (4) At room temperature, the Sb and Al co-doped synergistically modified O3-type nickel-manganese-based sodium ion battery cathode material NaNMSA has a first discharge capacity of 128 mAh / g at a current density of 0.1C in the voltage range of 2.0-4.0 V (e.g. Figure 3 ), the capacity retention rate is 85% after 100 cycles at 1C rate, which is much higher than the capacity retention rate of unmodified NaNM material (74.6%) (e.g. Figure 4 In addition, the discharge capacity at different rates is also higher than that of the unmodified material NaNM (as shown in Figure 5 As shown). In summary, the Sb and Al co-doped synergistically modified O3-type nickel-manganese-based sodium ion battery positive electrode material has high specific capacity, excellent cycle stability, and good rate performance, reflecting excellent electrochemical performance.
[0033] Example 2
[0034] (1) Based on the synthesis of 10g of Na 0.98 (Ni 0.4 Mn 0.5 Fe 0.1 ) x Sb y Al z O 2 The molar ratio of Mn, Ni, Fe, Sb and Al elements in (x+y+z=1) was calculated by weighing the corresponding manganese nitrate, nickel nitrate, iron nitrate, antimony chloride and aluminum nitrate, respectively, and dissolved in 200 mL of deionized water. 7.554 g of sodium acetate (3% excess) was added and magnetic stirring was performed. After the transition metal salt was dissolved, 3 g of ethylene glycol was weighed and added to the solution. The solution was evaporated to dryness under magnetic stirring at 110°C to obtain a wet gel.
[0035] (2) The wet gel obtained in step (1) is vacuum dried at 120° C., ground, sintered at 500° C. for 8 hours in an oxygen atmosphere, and then sintered at 925° C. for 15 hours, with the heating and cooling rates both being 5° C. / min. After cooling to room temperature, Sb and Al co-doped synergistically modified O3-type nickel-manganese-based sodium ion battery positive electrode material NaNMFSA is obtained.
[0036] (3) Similarly, in the case of a pure phase O3 type nickel-manganese based sodium ion battery positive electrode material, no Sb source and Al source are added in step 1, and the remaining steps are the same, thereby obtaining a pure phase O3 type nickel-manganese based sodium ion battery positive electrode material NaNMF.
[0037] (4) X-ray powder diffraction (XRD) analysis shows that the obtained product NaNMFSA maintains a similar structure to pure NaNMF and both belong to the O3-type layered structure with a space group of R-3m. In addition, both have high crystallinity. From the scanning electron microscope (SEM) image, it can be seen that the NaNMF material presents a plate-like morphology and is aggregated in large quantities. At the same time, a large amount of NiO phase is precipitated on the surface. After modification, the surface is smooth and the NiO impurity phase is reduced, indicating that the synergistic modification of Sb and Al co-doping inhibits the precipitation of NiO phase, which has an important influence on the subsequent electrochemical performance.
[0038] (5) At room temperature, the Sb and Al co-doped synergistically modified O3-type nickel-manganese-based sodium-ion battery positive electrode material NaNMFSA has an initial discharge capacity of 130mAh / g at a current density of 0.1C in the voltage range of 2.0-4.0V, and a capacity retention rate of 86.3% after 100 cycles at a rate of 1C, which is much higher than the capacity retention rate of the unmodified NaNMF material (72%). In addition, the discharge capacity at different rates is also higher than that of the unmodified material NaNMF. In summary, the Sb and Al co-doped synergistically modified O3-type nickel-manganese-based sodium-ion battery positive electrode material has high specific capacity, excellent cycle stability, and good rate performance, reflecting excellent electrochemical performance.
[0039] Example 3
[0040] (1) Based on the synthesis of 10g of Na 0.88 (Ni 0.4 Mn 0.5 Cu 0.1 ) x Sb y Al z O 2 The molar ratio of Mn, Ni, Cu, Sb and Al elements in (x+y+z=1) was calculated by weighing the corresponding manganese sulfate, nickel sulfate, copper sulfate, antimony oxide and aluminum nitrate, respectively dissolving them in 200 mL of deionized water, adding 7.7 g of sodium acetate (5% excess), and stirring magnetically. After the transition metal salt was dissolved, 5 g of tartaric acid was weighed and added to the solution, and evaporated to dryness at 120° C. with magnetic stirring to obtain a wet gel.
[0041] (2) The wet gel obtained in step (1) is vacuum dried at 120° C., ground, sintered at 550° C. for 8 hours in an air atmosphere, and then sintered at 950° C. for 16 hours, with the heating and cooling rates both being 10° C. / min. After cooling to room temperature, Sb and Al co-doped synergistically modified O3-type nickel-manganese-based sodium ion battery positive electrode material NaNMCSA is obtained.
[0042] (3) Similarly, for the pure phase O3 type nickel manganese based sodium ion battery positive electrode material, no Sb source and Al source are added in step 1, and the remaining steps are the same, thereby obtaining the pure phase O3 type nickel manganese based sodium ion battery positive electrode material NaNMC.
[0043] (4) X-ray powder diffraction (XRD) analysis shows that the obtained product NaNMCSA maintains a similar structure to pure NaNMC and both belong to the O3-type layered structure with a space group of R-3m. In addition, both have high crystallinity. From the scanning electron microscope (SEM) image, it can be seen that the NaNMC material presents a plate-like morphology and is aggregated in large quantities. At the same time, a large amount of NiO phase is precipitated on the surface. After modification, the surface is smooth and the NiO impurity phase is reduced, indicating that the synergistic modification of Sb and Al co-doping inhibits the precipitation of NiO phase, which has an important influence on the subsequent electrochemical performance.
[0044] (5) At room temperature, the Sb and Al co-doped synergistically modified O3-type nickel-manganese-based sodium-ion battery positive electrode material NaNMCSA has an initial discharge specific capacity of 132.2 mAh / g at a current density of 0.1C in the voltage range of 2.0-4.0 V, and a capacity retention rate of 87.2% after 100 cycles at a rate of 1C, which is much higher than the capacity retention rate of the unmodified NaNMC material (73.2%). In addition, the discharge specific capacity at different rates is also higher than that of the unmodified material NaNMC. In summary, the Sb and Al co-doped synergistically modified O3-type nickel-manganese-based sodium-ion battery positive electrode material has high specific capacity, excellent cycle stability, and good rate performance, reflecting excellent electrochemical performance.
[0045] Comparative Example 1
[0046] (1) According to the synthesis of 10g of NaNi 0.5 Mn 0.5 O 2 The corresponding manganese acetate and nickel acetate are weighed in a molar ratio of Mn and Ni elements, and dissolved in 200 mL of deionized water respectively. 2% excess sodium acetate is added and magnetic stirring is performed. After the transition metal salt is dissolved, 1 g of citric acid is weighed and added to the solution. The solution is evaporated to dryness at 100° C. with magnetic stirring to obtain a wet gel.
[0047] (2) The wet gel obtained in step (1) is vacuum dried at 120° C., ground, sintered at 450° C. for 6 hours in an argon atmosphere, and then sintered at 900° C. for 12 hours, with the heating and cooling rates both being 2° C. / min. After cooling to room temperature, a pure phase O3-type nickel-manganese-based sodium ion battery positive electrode material NaNM is obtained.
[0048] (3) X-ray powder diffraction (XRD) analysis shows that the obtained product pure NaNM maintains an O3-type layered structure with a space group of R-3m. In addition, the crystallinity is high (e.g. Figure 1 As shown in Figure 2). From the scanning electron microscope (SEM) image, we can see that the NaNM material has a plate-like morphology and is aggregated in large quantities, and a large amount of NiO phase is precipitated on the surface (as shown in Figure 2). Figure 2 shown).
[0049] (4) At room temperature, the first discharge capacity of the pure phase O3-type nickel-manganese-based sodium ion battery positive electrode material NaNM at a voltage range of 2.0-4.0V and a current density of 0.1C is 118.5mAh / g (e.g. Figure 3 ), the capacity retention rate after 100 cycles at 1C rate is 74.6%, which is much lower than the capacity retention rate of the modified NaNMSA material (such as Figure 4 In addition, the discharge capacity at different rates is also lower than that of the modified material NaNMSA (as shown in Figure 5 As shown). In summary, the O3-type nickel-manganese-based sodium-ion battery positive electrode material modified by co-doping with Sb and Al has high specific capacity, excellent cycle stability, and good rate performance, reflecting excellent electrochemical performance.
[0050] The above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a bimetallic Sb and Al co-doped synergistically modified O3 type nickel-manganese-based sodium ion battery positive electrode material, characterized in that: The following steps are involved: 1) Dissolve sodium salt, nickel salt, manganese salt, M salt, Sb source and Al source in deionized water respectively, and stir continuously; the sodium salt, nickel salt, manganese salt, M salt, Sb source and Al source are in accordance with the chemical formula Na x (Ni a Mn b M c )Sb d Al e O 2, Where x, a, b, c, d, e are molar numbers, 0.78<x<1, 0.2<a<1, 0.2<b<1, 0.2<c<1, 0<d<1, 0<e<1, a+b+c+d+e=1; 2) After the metal salt in step 1) is dissolved, the weighed additive is added, and the mixture is stirred and evaporated to dryness at 100-120° C. to obtain a wet gel; 3) vacuum drying and grinding the wet gel obtained in step 2), sintering at 450-550° C. for 6-8 hours under different atmospheres, and then sintering at 900-950° C. for 12-16 hours, with the heating and cooling rates both being 1-10° C. / min; cooling to room temperature to obtain a bimetallic Sb and Al co-doped synergistically modified O3-type nickel-manganese-based sodium ion battery positive electrode material.
2. The preparation method according to claim 1, characterized in that: In step 1), the sodium salt, nickel salt, manganese salt and M salt are all one or more of acetate, nitrate and sulfate.
3. The preparation method according to claim 1, characterized in that: In step 1), M is one or more metal ions selected from the group consisting of Cu, Fe, Mg, Zn, Ti and Co.
4. The preparation method according to claim 1, characterized in that: In step 1), the Sb source is one or more of antimony oxide and antimony chloride.
5. The preparation method according to claim 1, characterized in that: In step 1), the Al source is one or more of aluminum nitrate and aluminum oxide.
6. The preparation method according to claim 1, characterized in that: In step 2), the additive is one or more of citric acid, ethylene glycol and tartaric acid; the amount of the additive is 10 to 50% of the mass of the metal salt.
7. The preparation method according to claim 1, characterized in that: In step 3), the temperature of the vacuum drying is 120-130°C.
8. The preparation method according to claim 1, characterized in that: In step 3), the different atmospheres are air atmosphere, oxygen atmosphere or argon atmosphere.
9. The preparation method according to claim 1, characterized in that: For the pure-phase O3 type nickel-manganese-based sodium-ion battery positive electrode material, no Sb source and Al source are added in step 1, and the remaining steps are the same to obtain the pure-phase O3 type nickel-manganese-based sodium-ion battery positive electrode material.
10. The preparation method according to any one of claims 1 to 8 prepares a bimetallic Sb and Al co-doped synergistically modified O3 type nickel-manganese-based sodium ion battery positive electrode material, characterized in that: Doping with high-valent Sb elements promotes Ni 2+ / Ni 3+ The redox couple is activated, thereby improving the reversible capacity of the material; Al doping increases the bond energy of the TM-O bond, thereby improving the cycle stability and air stability of the material, and the formed Al2O3 film improves the interface stability by reducing the contact between the material and the electrolyte; the O3-type nickel-manganese-based sodium ion battery positive electrode material is modified by co-doping with bimetallic Sb and Al to effectively improve the material's specific capacity, cycle performance, interface stability and rate performance.
Citation Information
Patent Citations
High-entropy doped O3 phase layered oxide and preparation method thereof, sodium ion battery positive electrode material and battery
CN116605918A
Doped high-voltage positive electrode material, synthesis method and application in sodium-ion battery
CN116666617A
Nickel-manganese-based layered oxide positive electrode material for sodium ion battery and preparation method of nickel-manganese-based layered oxide positive electrode material
CN117117197A
Cathode active material, method for preparing same, secondary battery, battery module, battery pack, and electric device
CN117716537A